Richard Farnworth, Samuel Fisher, and the Authority of Scripture Among Early Quakers. Issue 2 (December 2015) - Angell, Stephen W.
Abstract : This essay traces the development of Quaker doctrines of Scriptural authority, concentrating on the years between 1653 and 1662. Utilizing controversies conducted by Richard Farnworth and Samuel Fisher with a series of non-Quaker critics, this study focuses on four areas: the possible status of Quaker epistles as revelation; whether the Bible, for Quakers, was human words, or God's words, or both; Quaker views of the Scriptural canon; and Quaker views of the propriety of using the Bible to settle religious controversies. This essay finds that defenders of Quaker views of Scripture steadily were pressed away from their original radical, spiritualist stances on Scriptural authority, toward a more orthodox, ecumenical, Puritan-oriented construction of that issue.